2016
DOI: 10.1074/jbc.m115.706028
|View full text |Cite
|
Sign up to set email alerts
|

The Steroid Hormone 20-Hydroxyecdysone Enhances Gene Transcription through the cAMP Response Element-binding Protein (CREB) Signaling Pathway

Abstract: Animal steroid hormones regulate gene transcription through genomic pathways by binding to nuclear receptors. These steroid hormones also rapidly increase intracellular calcium and cyclic adenosine monophosphate (cAMP) levels and activate the protein kinase C (PKC) and protein kinase A (PKA) nongenomic pathways. However, the function and mechanism of the nongenomic pathways of the steroid hormones are unclear, and the relationship between the PKC and PKA pathways is also unclear. We propose that the steroid ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 73 publications
(50 reference statements)
1
25
0
Order By: Relevance
“…We observed that a continuous 20E signal could inhibit PKA-mediated phosphorylation of silkworm BR-C, which is similar to the findings of 20E inhibition on PKC-mediated phosphorylation of the new isoform (BrZ7) of H. armigera BR-C (11). Notably, our data reveal that the cAMP/PKA signaling pathway was enhanced by 20E treatment at the early response stage, consistent with a previous report showing that the cAMP/PKA signaling pathway is enhanced by 20E in H. armigera (39). Nevertheless, the cAMP/PKA pathway was attenuated at the late-response stage after 20E application.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that a continuous 20E signal could inhibit PKA-mediated phosphorylation of silkworm BR-C, which is similar to the findings of 20E inhibition on PKC-mediated phosphorylation of the new isoform (BrZ7) of H. armigera BR-C (11). Notably, our data reveal that the cAMP/PKA signaling pathway was enhanced by 20E treatment at the early response stage, consistent with a previous report showing that the cAMP/PKA signaling pathway is enhanced by 20E in H. armigera (39). Nevertheless, the cAMP/PKA pathway was attenuated at the late-response stage after 20E application.…”
Section: Discussionsupporting
confidence: 92%
“…A schematic representation of the mechanism by which 20E regulates PKCδ expression and EcRB1 phosphorylation. (1) 20E via ErGPCR1 and ErGPCR2, Gαq, PLC, calcium ion, and CaMKII signaling triggers USP1 phosphorylation and acetylation to modulate formation of EcRB1/USP1 transcription complex to bind on EcRE for 20E pathway gene transcription based on our previous studies (16,36). (2) 20E rapidly up-regulates PKCδ expression via EcRB1 and USP1.…”
Section: Methodsmentioning
confidence: 90%
“…A previous study showed that USP phosphorylation is necessary for it interacting with EcRB1 in H. armigera (16). In addition, acetylation of USP1 is also necessary for it interacting with EcRB1 (36). 20E induces phosphorylation of cyclin-dependent kinase 10 to promote EcRB1/USP1 complex formation (21).…”
Section: E Up-regulates Pkcδ Expression To Promote Apoptosis Duringmentioning
confidence: 98%
“…However, this behavior was not observed for S. littoralis larvae fed on all the other DEHP conditions as their food consumption was on contrary increased, while their body mass remained similar to that of control larvae. In vertebrates, several deleterious effects of DEHP have been reported, on gut or digestive glands, with induction of tumors (Chen et al 2017), genotoxicity (Kitamoto et al, 2015), disruption of cholesterol homeostasis, deregulation of the inflammatory response, and acceleration of atherosclerosis (Zhao et al 2016). As a result, DEHP may have induced digestive problems to S. littoralis larvae such as malabsorption or altered digestion, which could have been compensated by increased food intake.…”
Section: Effect Of Dehp On Post-embryonic Developmentmentioning
confidence: 99%